Branding Vietnam: A Product Space analysis of how export diversification can shape up the country's sustainable and innovative growth - Luong Thanh Tran; Andreas Freytag (Friedrich Schiller University Jena, Faculty of Economics and Business Administration, 2025)
Vietnam's path to sustainable and innovative growth increasingly depends on how effectively it diversifies and repositions its export portfolio in the global market, or how the country "brand" itself through its exports to the world. Using data from UN Comtrade, we construct the Product Space model for Vietnam, visualizing the relatedness among the products in the country's export basket. Benchmarking against the Product Income Index (PRODY), the Product Gini Index (PGI), and the Product Complexity Index (PCI), we find that Vietnam's high-volume export products such as garments and textiles are hindering the country's development goals of sustainable growth, income equality, and innovation. Conversely, Vietnam has been able to export a number of small machine and precision equipment that yield higher added value in terms of sustainability and innovation, but these industries are lacking investment to scale up production. This suggests expansion strategies toward these precision tools and contraction for garments and textiles. Alternative options include radical innovation by shifting production to most knowledge-intensive products Vietnam is producing like cermet tools, or a moderate approach of pursuing export strategies of countries with slightly higher level of development than Vietnam.
Keywords: F14; F17; L7; O11; 330; Product Space; Product Complexity; Economic Complexity; PRODY; PGI; Innovation; Sustainability; Vietnam Export; Export Diversification; Export Product Targeting; Network Analysis